MEMBANGUN GENERASI MUDA BERINTEGRITAS: PROGRAM ANTI KORUPSI DI SMK SASMITA JAYA 1 - Helina, Inda; Mastanah, Mastanah; Rahmayanti, Sri; Windaningsih, Windaningsih; Rumiati, Rumiati; Fitria, Amin; Utaminingsih, Sri (Yayasan Education and Social Center, 2024)
The aim of carrying out this community service activity is for students to understand the forms of corruption and its aspects and change perceptions and attitudes towards corruption and form new skills and abilities aimed at fighting corruption. This activity uses the counseling method with lectures and discussions. The conclusion in this activity is the importance of socialization to build a young generation with integrity: the anti-corruption program through anti-corruption education is the cultivation of awareness of anti-corruption values ??which is applied from an early age with the aim of having good morals and character so that later they will not fall into acts of corruption. An anti-corruption attitude must be embedded in everyday life, including by always being honest in disciplined and responsible actions. Be it in the school, family or social environment. For this reason, we as agents of change strive to prevent acts of corruption that can harm ourselves and others. The importance of anti-corruption education in increasing the legal awareness of the younger generation in fostering anti-corruption behavior. The anti-corruption program is the cultivation of awareness of anti-corruption values ??which is implemented from an early age with the aim of having good morals and character so that later they will not fall into acts of corruption